Optimized sensorless control systems for cargo movement mechanisms - A. V. Sinyukov; T. V. Sinyukova; E. I. Gracheva; M. Kolcun; S. Valtchev (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. Investigation of the control system of the cargo movement mechanism when using different variants of sensorless control. The search for the optimal option, in which the formation of the speed is identical to the data obtained from the speed sensor. Analysis of the results obtained during the study, including the results obtained taking into account the heating of the motor windings.METHODS. The tasks set during the research are implemented by simulation modeling using the Matlab Simulink computer simulation environment.RESULTS. The article considers systems with different types of velocity observers. A system is implemented that takes into account the heating of the stator and rotor windings of an asynchronous motor, in which a non-adaptive observer and different types of neural network controller were introduced. A combined method of using neural network regulators is proposed.CONCLUSION. Sensorless control systems are relevant for use in industries with the presence, according to the conditions of the technological process, of high temperatures. The conducted research has shown that the use of neural network technologies allows you to work with settings of different levels and types. The proposed method, implying the use of joint work of neural network observers with various neurostructures, allows for speed testing in the entire range. The connection with cloud storage present in the proposed structure leads to the unloading of the management system, allowing to increase the process of analyzing data coming from the object.